2008
DOI: 10.1523/jneurosci.0443-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Modulation of GABAA Receptor Function by RNA Editing

Abstract: Adenosine-to-inosine (A-to-I) editing of RNA transcripts is an increasingly recognized cellular strategy to modulate the function of proteins involved in neuronal excitability. We have characterized the editing of transcripts encoding the ␣3 subunit of heteromeric GABA A receptors (Gabra3), in which a genomically encoded isoleucine codon (ATA) is converted to a methionine codon (ATI) in a region encoding the predicted third transmembrane domain of this subunit. Editing at this position (I/M site) was regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 29 publications
5
107
0
Order By: Relevance
“…Editing at the I/M Site of Gabra-3 Is Developmentally Regulated-We and others have previously shown that editing at the I/M site of Gabra-3 increases with age (4,21,23). It is also known that the ␣3 protein decreases during brain development (12).…”
Section: Resultsmentioning
confidence: 99%
“…Editing at the I/M Site of Gabra-3 Is Developmentally Regulated-We and others have previously shown that editing at the I/M site of Gabra-3 increases with age (4,21,23). It is also known that the ␣3 protein decreases during brain development (12).…”
Section: Resultsmentioning
confidence: 99%
“…Editing at the R/G site in the subunits of the glutamate receptor and the I/V site of the voltage-gated potassium channel Kcna1 results in functions that influence the kinetics of the receptors that are suitable for the mature brain. It has recently been suggested that editing of the alpha3 transcript Gabra3 results in receptors with slower activation and faster deactivation rates (Rula et al 2008). However, it is not known what effects this might have on the GABA A receptor in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the transcript of the human KCNA1 channel, an isoleucine codon is changed upon editing, but here the edited ITT codon is recognized as a valine (Bhalla et al 2004). Editing of both Gabra3 and KCNA1 has been suggested to have functional consequences on the receptors (Bhalla et al 2004;Rula et al 2008). The editing enzyme ADARB1 edits its own premRNA within intron 4 to induce alternative splicing (Rueter et al 1999).…”
mentioning
confidence: 99%
“…However, the second aspect is also essential, in that the extent of RNA editing readily exerts biological consequences. Importantly, alteration of editing levels during development or disease could have profound functional impacts (Paz et al 2007;Gallo and Galardi 2008;Rula et al 2008;Wahlstedt et al 2009;Silberberg et al 2012). In addition, the same issue exists in the analysis of allele-specific expression, where the allelic ratios of genetic variants in the expressed RNA need to be estimated accurately.…”
Section: Read Mapping Stringency Improves Accuracy In Estimated Rna Ementioning
confidence: 99%